(3GdEYQGH GdcHjQs - (3CMeO Hf eHGQc TGg GdMfajs
(3ChdgG (B:s
(3Ghdg bU jHJOF HCKfGA GdcdGe Ydi GjI (B( (3eGdc jhe GdOjf (B) (3ef ShQI GdaGJMI s
(3BNQgG (B:s
(3jfJgi CKfGA GdcdGe Ydi bhdg JYGdi (B( (3jNGOYhf Gddg hGdPjf CefhG(B) (3GdGjI ef ShQI GdHbQI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3GdfSNI fGbUI GdChd s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs